Features of water recreational and health complexes in Ukraine (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
Today, attention to health has become not only a concern for one's future, but also a lifestyle. Everyone wants to be healthy, athletic, slim, beautiful and joyful, living in harmony with the world around them. There are plenty of ways to keep fit: many people run in the morning, go to the fitness center, follow a diet and fight against bad habits. Technologies and equipment in the beauty sector are constantly improving, and entire industries have emerged on the basis of the general passion for health, one of which is wellness. Today, the world is striving for natural methods of treatment and health maintenance. The idea of vacation as an opportunity for natural healing fits perfectly with people's stereotypes and needs. More and more people are willing to combine recreation with health and appearance care, so the topic of building water recreation facilities is relevant today not only for health and beauty industry professionals, but also for those involved in investment, construction, operation and management of hotels. In this regard, the right location for the construction of sanatoriums and resorts plays an important role. Beautiful landscapes, clean air and healing mineral waters make balneological resorts a great place to spend a vacation. A pleasant, carefree vacation there can be combined with healthy treatments.
Keywords: recreational complexes; resort; hotel; health improvement; interior; sanatorium; tourism; architecture; wellness; spa